(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Diabetic nephropathy is a serious complication of diabetes mellitus, characterized by kidney damage due to prolonged high blood sugar levels. Monitoring kidney function is crucial in managing diabetic nephropathy, and cystatin C has emerged as a promising biomarker for assessing renal function. This study aimed to investigate the relationship between cystatin C levels and glycated hemoglobin in diabetic nephropathy patients, categorized based on their glomerular filtration rate (GFR) calculated using creatinine-cystatin C.